Peste des Petits Ruminants Risk Factors and Space-Time Clusters in Bangladesh - Rahman, A. K. M. Anisur; Islam, Sk Shaheenur; Sufian, Md. Abu; Talukder, Md. Hasanuzzaman; Ward, Michael P.; Martínez-López, Beatriz (Frontiers in Veterinary Science, 2021)
Peste des Petits Ruminants (PPR) is endemic in Bangladesh but its spatial distribution and risk factors have not yet been reported. Our aims for this study were to describe PPR time-space clusters, determine risk factors and develop predictive PPR risk maps using four years of passive surveillance data between 2014 and 2017 at the national level. We collected PPR case records  mainly based on presumptive diagnosis of small ruminants in sub district veterinary hospitals and sheep and goats population data from all 64 districts of Bangladesh. We calculated PPR cumulative incidence per 10,000 animals at risk per district, conducted cluster (Moran’s spatial autocorrelation and scan statistics) and hotspot analysis (local indicator of spatial association statistic) and created predictive maps for each year and all four years combined. The association between PPR cumulative incidence and hypothesized risk factors  including climatic variables, elevation, road length, river length, railroad length, land cover and water bodies  was analyzed using a geographically weighted regression model. About 5.2 million PPR cases in small ruminants were reported during the four-year study period. The highest number of PPR cases were reported during the monsoon season (27.6%). The highest and lowest number of cases were reported from Rajshahi (36.1%) and Barisal divisions (2.1%), respectively. Five space-time clusters, 9 local highhigh clusters and 9 hotspots were identified. Higher cumulative incidences of PPR were consistently predicted in north-east, north-west and south-east parts of Bangladesh. Road length (P=0.03) was positively associated with PPR incidence in Bangladesh. Results suggest that movement of animals (road length) plays an important role in the epidemiology of PPR in Bangladesh. Along with restriction of animal movement, hotspots and highhigh clusters should be targeted first for vaccination coverage in Bangladesh and similar PPR endemic countries to achieve eradication.